Audit of a computerized version of the Manchester triage system and a SIRS-based system for the detection of sepsis at triage in the emergency department - Dewitte, Ken; Scheurwegs, Elyne; Van Ierssel, Sabrina; Jansens, Hilde; Dams, Karolien; Roelant, Ella (International journal of emergency medicine, 2022)
Background and importance Different triage systems can be used to screen for sepsis and are often incorporated into local electronic health records. Often the design and interface of these digitalizations are not audited, possibly leading to deleterious effects on screening test performance. Objective To audit a digital version of the MTS for detection of sepsis during triage in the ED. Design A single-center retrospective study Settings and participants Patients ( n =29766) presenting to an ED of a tertiary-care center who received formal triage were included. Outcome measures and analysis Calculated performance measures included sensitivity, specificity, likelihood ratios, and AUC for the detection of sepsis. Errors in the application of the specific sepsis discriminator of the MTS were recorded. Main results A total of 189 (0.7%) subjects met the Sepsis-3 criteria, with 47 cases meeting the criteria for septic shock. The MTS had a low sensitivity of 47.6% (95% CI 40.3 to 55.0) for allocating sepsis patients to the correct triage category. However, specificity was high at 99.4% (95% CI 99.3 to 99.5).